Novel drugs in the management of acute mountain sickness and high altitude pulmonary edema - Sikri G; Bhattacharya A (Open Access Journal of Sports Medicine, 2015)
Gaurav Sikri, Anirban Bhattacharya Department of Physiology, Armed Forces Medical College, Wanowarie, Pune, IndiaWe read with great interest the review article titled “Wilderness medicine at high altitude: recent developments in the field” by Shah et al.1 The authors have comprehensively summarized the recent advances in the field of high altitude medicine relevant to sports and travel medicine. However, Shah et al have described potential drugs for management of high-altitude illnesses, such as acute mountain sickness (AMS), high altitude cerebral edema, and high altitude pulmonary edema (HAPE) as one group under the section “Novel drug treatment for AMS”. The pathophysiologies of these two sets of diseases (AMS/high altitude cerebral edema as one and HAPE as another set) are different2 and hence it would have been nice to have had the novel drugs described separately to elucidate the therapeutic approach for the two different classes of diseases.View original paper by Shah et al.